Improvement of Respiratory Depression in a Patient with Primary Medullary Hemorrhage Following Removal of Hematoma in the Half-sitting Position - Ichimura, Shinya; Bertalanffy, Helmut; Nakaya, Masato; Mochizuki, Yoichi; Fukaya, Raita; Moriwaki, Goroku; Fukuchi, Masahito; Fujii, Koji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Primary medullary hemorrhage is a rare event that may result in ataxic respiration. Although it remains controversial whether primary medullary hemorrhage should be managed conservatively or surgically, recent advancements in neuroimaging and microsurgical techniques have shown promise for improving outcomes and prognosis following surgery. The present report discusses the case of a 70-year-old woman admitted to our institution due to sudden-onset nausea and vomiting. The patient underwent surgical removal of a right medullary hematoma for the treatment of daytime respiratory depression and nocturnal apnea while in the half-sitting position. Following surgery, her spontaneous respiration improved, and she was discharged with independent gait. Despite the risk of venous air embolism, accumulating evidence suggests that the half-sitting position is suitable for brainstem surgery because gravity-assisted blood and irrigation drainage from the surgical field allows for cleaner dissection and reduces the need for bipolar coagulation.
Keywords: primary medullary hemorrhage; respiratory depression; half-sitting position